2021
DOI: 10.1101/2021.03.15.435370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Codependency and mutual exclusivity for gene community detection from sparse single-cell transcriptome data

Abstract: Single-cell RNA-seq (scRNA-seq) can be used to characterize cellular heterogeneity in thousands of cells. The reconstruction of a gene network based on coexpression patterns is a fundamental task in scRNA-seq analyses, and the mutual exclusivity of gene expression can be critical for understanding such heterogeneity. Here, we propose an approach for detecting communities from a genetic network constructed on the basis of coexpression properties. The community-based comparison of multiple coexpression networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…S5E). To evaluate codependency and mutual exclusivity for Atoh1 , Ascl1 , and other genes in proliferative NPCs, we calculated the codependency index (CDI) and exclusively expressed index (EEI) ( 29 ). We found that Atoh1 and Ascl1 were expressed in a mutually exclusive manner among proliferative NPCs (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5E). To evaluate codependency and mutual exclusivity for Atoh1 , Ascl1 , and other genes in proliferative NPCs, we calculated the codependency index (CDI) and exclusively expressed index (EEI) ( 29 ). We found that Atoh1 and Ascl1 were expressed in a mutually exclusive manner among proliferative NPCs (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proliferative NPCs were digitally isolated from scRNA-seq data, and the coexpressed and mutually exclusive gene pairs were calculated ( 29 ). The gene pairs containing Atoh1 or Ascl1 with high CDI (CDI > 10.0) and EEI (EEI > 3.0) are shown in data S3.…”
Section: Methodsmentioning
confidence: 99%
“…Differential expression analyses were performed using Wilcoxon rank sum (Wilcox) and codependency index (CDI) 61,62 . The Wilcox method was implemented using the wilcoxauc function ( Presto R package, v 1.0.0) 63 .…”
Section: Methodsmentioning
confidence: 99%
“…CDI is then defined as: We further normalized the CDI score using the CDI score corresponding to the probability of observed a perfect co-dependency for cluster k : where π k,k = P ( c k = 1, c k = 1), under the assumption of independence. Possible values of nCDI range between [0,1], such that nCDI = 1 represents perfect co-dependence between a gene and cluster, and nCDI = 0 represents no co-dependence but is not equivalent to mutual exclusivity which has been formulated elsewhere 62 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation